The Influence of Leadership Behavior and Organizational Justice on Lecturer Performance - Musyafak Musyafak; Sanaji Sanaji; Andre Dwijanto Witjaksono; Anang Kistyanto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Basically, every educational institution has a certain vision and mission that must be achieved. To achieve each goal, it encourages educational institutions to maximize the performance of teachers in achieving organizational goals. However, the existence of deviant leadership behavior outside of authority can be an obstacle in achieving organizational goals. This can occur because such behavior is deliberately done to disrupt the smooth running of the organization and justice in the work environment is increasingly recognized as an important factor in achieving optimal performance. This study is intended to examine how leadership behavior and organizational justice in higher education affect lecturers' performance behavior. Using 100 respondents from higher education institutions in Surabaya, leadership behavior and organizational culture were examined for their impact on lecturer performance. The method of analysis applied in this study is a quantitative approach using multiple regression, with validity and reliability testing of each variable in question as well as classical assumption tests before the best research model is obtained. All results support the effects studied. Leadership behavior and organizational justice have a real impact on lecturer performance. These findings are consistent with the proposed hypothesis, confirming the importance of the role of leaders and a fair organizational culture in improving lecturer performance.